Fighting the VAT Gap – The Polish Experience - Brodzka, Alicja; Biernacki, Krzysztof (Publishing House of Wroclaw University of Economics and Business, 2024)
Quote as: Brodzka, A., & Biernacki, K. (2024), Fighting the VAT Gap – the Polish Experience. In P. Luty, N. Versal, & P. Semerád (Eds.), Knowledge and Digitalisation Against Corruption and Fraud (pp. 88-100). Publishing House of Wroclaw University of Economics and Business.
s. 104
Keywords: corruption; welfare fraud; VAT gap; payment systems; shadow economy